Relationship between cyberbullying roles, cortisol secretion and psychological stress - González-Cabrera, Joaquín; Calvete, Esther; León-Mejía, Ana; Pérez-Sancho, Carlota; Peinado, José M. (Computers in Human Behavior, 2017)
Although cyberbullying is associated with different psychological problems, the role of biological markers of stress in cyberbullying has been relatively neglected. The aims of this study were: 1) to analyze the profile of cortisol secretion along the day in subjects involved in cyberbullying and 2) to investigate whether the predictive relationship between cyberbullying victimization and subjective symptoms of stress and anxiety are accounted for by cortisol reactivity. A longitudinal study was conducted to investigate the potential correlation between cyberbullying, anxiety and perceived stress assessed at two time points (four-month interval). In the second wave, daily salivary cortisol levels were measured (Salivette) and examined as a potential biochemical marker of stress. The results suggest that patterns of cortisol release as measured using the area under the curve (AUC) and perceived stress are related to roles in cyberbullying. Cybervictims and cyberbully-victims exhibited higher cortisol secretion levels and greater perceived stress, as compared to cyberbullies and cyberbystanders. In addition, analyses of indirect effects revealed that the predictive relationships between cyberbullying victimization at Wave 1 and anxiety and perceived stress at Wave 2 are explained by higher AUC values. In conclusion, the results obtained suggest that cyberbullying victimization may induce changes in the Hypothalamicpituitary-adrenocortical axis, as evidenced by the finding that cortisol reactivity is more severely disrupted in incidental victims and cyberbully-victims. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: stress; anxiety; cyberbullying; cortisol; victimization; JCR; Scopus